ANALISIS PENGARUH STRUKTUR MODAL, NILAI PERUSAHAAN, KINERJA KEUANGAN, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2020-2024 - Hutagalung, Sindy Aura Puspita Br; Parhusip, Austin Alexander (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study aims to analyze the effect of capital structure, firm value, financial performance, and dividend policy on stock prices in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative approach with an associative research type. The data used are secondary data obtained from financial statements through the official IDX website (https://www.idx.co.id). The population consists of 51 companies, of which 10 were selected as samples using purposive sampling, resulting in 50 observations. Data were analyzed using multiple linear regression analysis with a 5% significance level. The results show that, partially, capital structure, firm value, and financial performance have a significant effect on stock prices, while dividend policy has no positive and significant effect. Simultaneously, capital structure, firm value, financial performance, and dividend policy have a significant effect on stock prices. These findings indicate that investors tend to consider financial stability and company growth prospects rather than dividend distribution policies in making investment decisions.